Hallmarks of Human Small Antral Follicle Development: Implications for Regulation of Ovarian Steroidogenesis and Selection of the Dominant Follicle - Kristensen, Stine G.; Mamsen, Linn S.; Jeppesen, Janni V.; Bøtkjær, Jane Alrø; Pors, Susanne E.; Borgbo, Tanni; Ernst, Erik; Macklon, Kirsten T.; Andersen, Claus Yding (Frontiers in Endocrinology, 2018)
Regulation of human ovarian steroidogenesis differs from other species and precise knowledge on how human small antral follicles (hSAF) develop and acquire competence for continued growth and steroid output is still incomplete. The present study has characterized almost one thousand normal hSAF collected in connection with cryopreservation of ovarian tissue for fertility preservation. The antral follicles (ranging from 3 to 13 mm) were generally aspirated from one ovary surgically removed during the natural cycle, and the follicular fluid (FF) and the granulosa cells (GC) were isolated and snap-frozen. In FF the following hormones were measured: Inhibin-B, Inhibin-A, AMH, follistatin, PAPP-A, oestradiol, progesterone, testosterone and androstenedione. In GC, mRNA gene expressions using q-PCR were measured for the following genes: FSHR, AMH, CYP19 and AR. All samples in which one of the above parameters was measured were included, but typically multiple parameters were measured. Highly significant differences in concentration and follicular content in relation to follicular diameter were found for all measured hormones despite massive variability in-between follicles for any given diameter. The results demonstrate that profound changes take place in the hormonal microenvironment around follicular diameters of 8 to 11 mm corresponding to when follicular selection occurs. At this point, Inhibin-B and Inhibin-A showed distinct peaks concomitant with a significant reduction in both AMH protein and mRNA expression. Concentrations of inhibin’s, androgens, FSHR and AR were intimately associated and it is suggested that inhibin-B in combination with PAPP-A and thereby IGF2 activity exerts important paracrine signalling at follicular selection. At the same time up-regulation of oestradiol synthesis and CYP19 mRNA expression increase steroid output profoundly. Furthermore, the highly significant association between FSHR and AR mRNA gene expression enforces important functions of androgens in follicular development. Collectively, these data re-introduce the understanding of the follicular phase as two parted in which regulation of steroidogenesis differ. The profound changes taking place around follicular selection highlight important paracrine actions of TGF-β family members and IGFs for securing dominance of the selected follicle.